To what extent can blockchain network technology add value to car manufacturers’ businesses and stakeholders in Brazil? - Martins, Arthur Henrique Pontes (2022)
The automotive industry plays an important role for the global economy, both for developing and developed nations. Nowadays, the car manufacturing companies face significative disruptions in the sector which can be regarded as business opportunities or result in difficulties in case firms do not adapt fast and efficiently as it might be necessary. Simultaneously, new technologies, especially from the software realm and not only from the hardware side anymore, have been opening space for new creations, players, and innovative business models to arise in the industry. One of those new and promising technologies is the blockchain (BT) network and the possibility of building a digital ecosystem with different and untrusted stakeholders. Blockchain is a transactional database technology that relies on the internet as its framework base with distributed ledger technology (DLT) protocols that enables its attribute of storing data related to any kind of transaction in a peer-to-peer network, for individuals or entities, in a transparent (verifiable), chronological, consensual, and tamper-resistant manner. Through the analysis of the blockchain technology from a strategic perspective for multinational car manufacturing companies, combined with a focus on the Brazilian market challenges and opportunities, this paper studies the extent to which blockchain can add value to car manufacturers’ businesses and their respective stakeholders in general and goes deeper in the local market reality. This research applies a qualitative approach to further explore the yet not widely discussed topic in the automotive sector. It highlights how the main stakeholders from the OBMs’ ecosystems can benefit from blockchain’s through interviews with executives from the sector. It is concluded by this study that even though blockchain technology’s features are promising for the sector as it could benefit especially the clients, there are other pressing issues that must be addressed before, especially in Brazil. Considering the potential level of investment, capabilities, and the underlying risks of such an endeavor, other sectors are more likely to develop a BT solution due to a proximity to their core business and offer to OBMs as a solution. This thesis is organized in the following sequence: introduction, literature review, methodology, findings and discussion, and conclusion.